A Comparative Study on the Effectiveness of Passive and Free Cooling Application Methods of Phase Change Materials for Energy Efficient Retrofitting in Residential Buildings. (2017) - Alam, Morshed; Sanjayan, Jay; Zou, Patrick X.W.; Ramakrishnan, Sayanthan; Wilson, John
Abstract: This study compared the effectiveness of passive and free cooling application methods of Phase change materials (PCMs) when used as energy efficient retrofitting in a residential building. A modern duplex residential building in Melbourne, Australia was considered for the case study. In passive application, PCM was installed in the ceilings of the house. In free cooling application, outdoor air was supplied to the indoor after passing it through a PCM storage unit. The study was carried out using building simulation software EnergyPlus V8.4 and computational fluid dynamics (CFD) software ANSYS V15.1. The developed simulation models of passive and free cooling applications were validated using relevant experimental data. The validated simulation models were then used to investigate the effectiveness of these PCM application methods in the selected building. The results showed that, for the studied house, free cooling application of PCM is more effective than the passive application in reducing the internal zone temperature. Under typical summer climatic conditions of Melbourne, free cooling application resulted in up to 1.8 °C reduction in zone air temperature, compared to only 0.5 °C when PCM was applied as passive heat storage system. The outcome of this study would be helpful in selecting the effective PCM application method for these types of residential buildings in similar climates.